Acteoside ameliorates hepatocyte ferroptosis and hepatic ischemia-reperfusion injury via targeting PCBP2 - Kexin Jia; Yinhao Zhang; Fanghong Li; Runping Liu; Jianzhi Wu; Jiaorong Qu; Ranyi Luo; Zixi Huang; Zhe Xu; Xiaojiaoyang Li (Acta Pharmaceutica Sinica B)
Hepatic ischemia-reperfusion injury (HIRI) has been considered as an inevitable process of liver transplantation. Hepatocyte ferroptosis is a key factor in HIRI development, yet precise mechanism and potential therapies are still unclear. Here, we demonstrated a strong correlation between hepatocyte ferroptosis and the downregulation of poly(rC)-binding protein (PCBP2), which compromised the stability of antiporter system Xc– (consisted of SL3A2/SLC7A11). Besides, inhibiting PCBP2 contributed to facilitating cofactor p300 to enhance the transcriptional activity of HIF1α, leading to the expression and secretion of HMGB1. Then, released HMGB1 from ferroptotic hepatocytes worsened M1 macrophage recruitment and immune response during HIRI. Additionally, acteoside (ACT) was shown to assist PCBP2 in stabilizing the mRNA stability of Slc3a2 and Slc7a11, as well as enhance the binding affinity of PCBP2–system Xc–. Beyond that, ACT also supported PCBP2 to limit HMGB1-induced M1 macrophage recruitment through imposing restrictions on p300 and HIF1α. Furthermore, specific knockdown of PCBP2 in hepatocytes directly interposed the therapeutic efficacy of ACT on HIRI mice. In conclusion, ACT alleviated hepatocyte ferroptosis and HIRI via promoting PCBP2 to maintain the stability of system Xc– and limit HIF1α/p300–HMGB1 signaling. These findings highlight the therapeutic benefits of ACT in treating HIRI and offer insights into innovative therapeutic strategies.